Water-related citizens' complaints on a coastal wet land area: exploring the influence of local administrative boundaries - Carvalho, Daniela (2013)
This paper explores the water-related citizens’ complaints submitted to the municipalities surrounding ‘Ria de Aveiro’, a natural lagoon located in the center of Portugal close to the Atlantic coast, and is aimed at analyzing how local administrative boundaries might influence the frequency, typologies and territorial pattern of complaints. It also analyzes the frequency of water-related complaints in relation to other environmental problems raised by local population. The proposed analysis assesses how the existence of such a large water territory that ‘Ria de Aveiro’ is, influences the typologies of water-related complaints and the propensity of the population to complain about problems specifically related to the quality of this area. It also analyzes the relationship between the extent of the water body of ‘Ria the Aveiro’ within each municipality and the frequency of water-related complaints. The paper is organized into four sections. The first presents a brief literature review about citizen environmental complaints and their relevance for environmental and water resources governance, highlighting the role played by different sorts of stakeholders involved. The second section describes the case study and the methodology adopted. The results of the empirical study are presented in the third section with emphases given on the actors involved, the typologies of water-related problems referred to in the complaints, as well as, their territorial pattern. The final section critically analyses these results and questions the actual relevance of local administrative boundaries in the perception of water-resources related values as interpreted and communicated by citizens’ complaints.